Transnasal transpterygoid resection of meningoencephalocoele with abolition of seizures. Issue 9 (19th September 2019) - Spinos, Dimitrios; Unadkat, Samit; Nair, Ramesh; Grant, William
Abstract : Meningoencephalocoeles are herniations of intracranial contents through skull base defects. Patients may present with a plethora of symptoms ranging from cerebrospinal fluid (CSF) rhinorrhoea to epileptic convulsions, or indeed may be asymptomatic. We present a case of a 24-year-old man suffering from new onset, drug-resistant tonic–clonic seizures. Imaging studies revealed neural tissue and meninges protruding through the pterygoid portion of the sphenoid bone, into the anteromedial aspect of the middle cranial fossa. An image-guided endoscopic transnasal transpterygoid approach was carried out as a joint otolaryngological and neurosurgical procedure, resulting in the patient being seizure-free for over 12 months postoperatively. There is a paucity of literature supporting such an endoscopic approach to treat epilepsy secondary to a meningoencephalocoele. We illustrate that this is a safe and minimally invasive treatment option which ultimately rendered the patient free of all anticonvulsants.